Oczami dziecka, czyli porównanie szaty graficznej we współczesnych elementarzach (polskim i bułgarskim) dla pierwszoklasistów - Fąfara, Justyna (Slavica Lodziensia, 2019)
The paper examines the graphic and illustrative elements in contemporary Polish and Bulgarian alphabet books. The comparative approach reveals basic similarities and significant differences between the selected textbooks concerning the preferred thematic fields in the primary education process in both countries. The analysis allows to differentiate the prevailing motives and values depicted in the textbooks (such as family and social relations, national symbols, modern technologies), the strategies of presenting the letters of the alphabet, the leading book characters, etc.